2018
DOI: 10.1111/plb.12672
|View full text |Cite
|
Sign up to set email alerts
|

Plant organ senescence – regulation by manifold pathways

Abstract: Senescence is the final stage of plant ontogeny before death. Senescence may occur naturally because of age or may be induced by various endogenous and exogenous factors. Despite its destructive character, senescence is a precisely controlled process that follows a well-defined order. It is often inseparable from programmed cell death (PCD), and a correlation between these processes has been confirmed during the senescence of leaves and petals. Despite suggestions that senescence and PCD are two separate proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 192 publications
1
62
0
1
Order By: Relevance
“…AsA alleviated the damage of ROS: ROS are unavoidable byproducts of cellular metabolism (Xu et al 2017). Plants produce more ROS during aging process (Wojciechowska et al 2018). If the balance of ROS generation and scavenging is destroyed, excess ROS would attack cell components, such as chloroplasts and cell membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AsA alleviated the damage of ROS: ROS are unavoidable byproducts of cellular metabolism (Xu et al 2017). Plants produce more ROS during aging process (Wojciechowska et al 2018). If the balance of ROS generation and scavenging is destroyed, excess ROS would attack cell components, such as chloroplasts and cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…We compared the expression levels of SAGs, which are believed to be useful molecular markers for leaf senescence, among the three lines during ET-induced aging process (Hensel et al 1993, Wojciechowska et al 2018. The results showed that the expression of SAG2, SAG12, SAG13, SAG20, SAG21 were all at low level and there were no significant differences between them before ethephon spraying.…”
Section: Relative Expression Of Senescence-associated Genesmentioning
confidence: 99%
“…senium -старение). Сеникация посевов зерновых культур приводит к медленному отмиранию листьев, сходному с естественным старением (15). Механизм действия сениканта заключается в ускорении обмена веществ в тканях растений и повышении скорости оттока пластических веществ из листьев и стеблей в метелку (колос).…”
Section: регуляция оттока ассимилятов в зерновки для повышения продукunclassified
“…In crops, this process usually overlaps with the reproductive phase and might influence reducing crop yield when it is induced prematurely or/and under unfavorable environmental conditions [2]. The onset of senescence may be related to age [3,4] or can be stimulated by internal factors, such as reactive oxygen species (ROS) or changes in phytohormone level, as well as external factors such as photoperiod, temperature, nutrient deficiency, or shading [5][6][7][8]. While the process of senescence appears to be outwardly destructive, the fact that it is a highly regulated process allows plants to relocate a significant portion of valuable nutrients from senescing organs to other tissues so that they can be re-utilized rather than lost [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most characteristic features of senescence is an increase of catabolic metabolic reactions in relation to anabolic ones [11]. This shift leads to the degradation of individual organelles and eventually the rupture of the tonoplast, protoplast acidification, and cell death [8,[12][13][14]. Chloroplasts, which contain approximately 80% of total leaf nitrogen, are one of the first organelles to be degraded [15,16].…”
Section: Introductionmentioning
confidence: 99%